2020
DOI: 10.1155/2020/5052840
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Induces Reduction in Limbic-Cortical Feedback of a Neuralgia Rat Model: A Dynamic Causal Modeling Study

Abstract: Background. Neuropathic pain after brachial plexus avulsion remained prevalent and intractable currently. However, the neuroimaging study about neural mechanisms or etiology was limited and blurred. Objective. This study is aimed at investigating the effect of electroacupuncture on effective connectivity and neural response in corticolimbic circuitries during implicit processing of nociceptive stimulus in rats with brachial plexus pain. Methods. An fMRI scan was performed in a total of 16 rats with brachial pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…A study regarding neuropathic pain suggested that acupuncture intervention reduced EC from hypothalamus and amygdala to somatosensory cortex which might be one of the mechanisms underlying the pain relief. 55 We discovered that compared to the sham-EA group, the right septum to the left septum-directed connectivity was increased, whereas the left septum to the right septum-directed connectivity was decreased in the EA group. The results extended connectivity findings by delineating the direction of influence between the right septum and the left septum.…”
Section: Discussionmentioning
confidence: 81%
“…A study regarding neuropathic pain suggested that acupuncture intervention reduced EC from hypothalamus and amygdala to somatosensory cortex which might be one of the mechanisms underlying the pain relief. 55 We discovered that compared to the sham-EA group, the right septum to the left septum-directed connectivity was increased, whereas the left septum to the right septum-directed connectivity was decreased in the EA group. The results extended connectivity findings by delineating the direction of influence between the right septum and the left septum.…”
Section: Discussionmentioning
confidence: 81%
“…A previous study has shown that EA on Jiaji (EX-B2) can treat neuropathic pain. [ 37 ] Yet, as far as we know, no evidence for Zhigou (TE6) and Houxi (SI3) is observed.…”
Section: Discussionmentioning
confidence: 89%
“…A dynamic causal modeling study found that harmful stimuli are likely driven by the somatosensory cortex, propagating bidirectionally with the hypothalamus and amygdala, as well as their interactions. In contrast, needling reduced limbic–cortical feedback in a rat model of NP ( Ma et al, 2020 ). Functional magnetic resonance imaging (fMRI) of the resting neural network showed reduced dlPFC and ACC activity in patients with chronic sciatica.…”
Section: Brain Mechanisms Involved In the Treatment Of Np By Using Ac...mentioning
confidence: 99%